Structural and optical properties of gold nanosphericals in variation of growth time using seed mediated growth method - Mohamed Ali, Nor Salihah; Ibrahim, Farah Nur Diyana; Morsin, Marlia; Mat Salleh, Muhammad; Jumadi, Nur Anida; Morsin, Marriatyi (UTEM, 2017)
Nanogold is a type of metallic nanostructures and it is very sensitive to the dielectric environment of the materials due to strong dependency of plasmon on shapes and sizes. The unique properties of gold nanostructures can be implemented as sensing material in Localized Surface Plasmon Resonance (LSPR) sensor. This paper reports an experimental study on growth time effect towards structural and optical properties of gold nanosphericals (AuNSs). The gold nanoplates have been grown on a substrate using seed mediated growth method (SMGM). In this study, the growth time was varied from 30 minutes to seven hours. The largest size of AuNSs is ~ 82.67 nm obtained from 7 hours growth time sample. XRD analysis shows a peak of the diffraction angle occurs at the plane (111) in position ~ 38.19º. The optical absorption spectra of all samples show resonance peaks in the range of 530 nm to 560 nm, which are corresponding to the transverse surface plasmon resonance (t-SPR). Thus, in this study, it was found that the growth time affected the growth of the gold nanostructures with optimum growth time of seven hours. Longer growth time resulted in the larger size of AuNSs and therefore, it is not very suitable to be used in LSPR sensing application.